Occurrence map of broad-band auroral VLF hiss observed by ISIS satellites - Ondoh, Tadanori (National Institute of Polar Research, 1988)
P(論文) A polar map of occurrence rate of broad-band auroral VLF hiss is drawn by using narrow-band VLF intensity data of 6 frequencies which were processed from ISIS electric field (50Hz-30kHz) tapes of 347 passes received at Syowa Station, Antarctica from June 1976 to January 1983.The high-latitude contour of occurrence rate of 0.3 lies at invariant latitude of about 82° for all local times. The low-latitude contour of 0.3 lies at 74° around 10h geomagnetic local time (MLT) and it extends down to 67° around 22h MLT, showing a symmetricity with respect to the 10-22h MLT meridian. Two regions of high occurrence rate above 0.5 lie between 76° and 78° in the afternoon sector and also between 78° and 81° in the late night-morning sector. The result is not consistent with the occurrence map of auroral hiss at 9.6kHz with a pronounced dawn-dusk asymmetry obtained from Ariel magnetic field data by HUGHES et al. (Space Research XI, ed. by K. Ya. KONDRATYEV et al. Berlin, Akademie, 1323-1330,1971). This discrepancy between the ISIS and Ariel results is discussed from view points of auroral particle precipitation and difference in VLF data used. departmental bulletin paper